2009
DOI: 10.1016/j.ejcts.2009.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte filtration of salvaged blood during cardiac surgery: effect on red blood cell function in concentrated blood compared with diluted blood

Abstract: Leucocyte filtration of the diluted salvaged blood during cardiac surgery does not affect RBC function, but it tends to deplete the ATP content of RBCs as the salvaged blood has been concentrated prior to filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Another crucial threat is the hypotension triggered by the LDF-treated blood [ 15 , 16 ], which might be associated with the elevation of bradykinin [ 16 ] and interleukin-6 [ 17 ] during the transfusion of salvaged blood treated by LDF. In addition, LDF also markedly decreased the ATP content in erythrocytes [ 18 ]. Thus, Hansen’s group advocated gamma irradiation to eliminate tumor-laden blood and found that 50 Gy irradiation was sufficient to inactivate tumor cells in blood shed during cancer surgery with a reduction rate exceeding 10 logs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another crucial threat is the hypotension triggered by the LDF-treated blood [ 15 , 16 ], which might be associated with the elevation of bradykinin [ 16 ] and interleukin-6 [ 17 ] during the transfusion of salvaged blood treated by LDF. In addition, LDF also markedly decreased the ATP content in erythrocytes [ 18 ]. Thus, Hansen’s group advocated gamma irradiation to eliminate tumor-laden blood and found that 50 Gy irradiation was sufficient to inactivate tumor cells in blood shed during cancer surgery with a reduction rate exceeding 10 logs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although all CS devices use the same theory of centrifugation and washing, this investigation clearly shows that the actual function of RBC products processed by different CSs varies significantly from one device to another. As mechanical processing affects the RBC function of salvaged blood (9,10), an important indicator of the performance of the CS is its capability to preserve RBC function as much as possible. The erythrocyte function test includes 2,3‐DPG as a surrogate for oxygen affinity, which is a major factor in tissue oxygen supply.…”
Section: Discussionmentioning
confidence: 99%